Astrocytes and absence epilepsy - (:unkn) unknown (WILEY, 2013)
This commentary discusses the importance of a new study entitled ONO-2506 inhibits spikewave discharges in a genetic animal model without affecting traditional convulsive tests via gliotransmission regulation' by Yamamura etal. () from Dr Okada's laboratory. The results from this study suggest that specific astrocyte modulating approaches should be developed for managing non-convulsive forms of epilepsy. In addition, the authors have advanced our understanding of astrocytic signalling and glial transmission. Their findings point to kynurenic acid as one of the key transmitters in the bi-directional communication between astrocytes and neurons. Linked Article This article is a commentary on the research paper by Yamamura etal., pp. 10881100 of this issue. To view this paper visit http://dx.doi.org/10.1111/j.1476-5381.2012.02132.x
Keywords: absence seizure; GAERS; astrocytic signalling; glial transmission; kynurenic acid; SEIZURES; DISCHARGES; MODEL; ILAE; RATS